2018
DOI: 10.1021/acschembio.8b00533
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationship of Flavin Analogues That Target the Flavin Mononucleotide Riboswitch

Abstract: The flavin mononucleotide (FMN) riboswitch is an emerging target for the development of novel RNA-targeting antibiotics. We previously discovered an FMN derivative, 5FDQD, that protects mice against diarrhea-causing Clostridium difficile bacteria. Here, we present the structure-based drug design strategy that led to the discovery of this fluoro-phenyl derivative with antibacterial properties. This approach involved the following stages: (1) structural analysis of all available free and bound FMN riboswitch str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 65 publications
(165 reference statements)
0
63
0
Order By: Relevance
“…The flavin mononucleotide (FMN) riboswitch is notable because it senses the cofactor FMN as well as the natural product roseoflavin, which acts as an antibacterial (23,127). This vulnerability has fostered efforts to target the JBC REVIEWS: Molecular recognition of HIV TAR RNA FMN riboswitch with novel antibiotics (19,21,22,25,26). Recent structure-guided design led to the discovery of compound BRX1555-an FMN analogue that binds with a K D of 39.0 Ϯ 0.7 nM based on in-line probing (Fig.…”
Section: Model Ncrna-inhibitor Interactions: Base Pairing and Shape Cmentioning
confidence: 99%
See 3 more Smart Citations
“…The flavin mononucleotide (FMN) riboswitch is notable because it senses the cofactor FMN as well as the natural product roseoflavin, which acts as an antibacterial (23,127). This vulnerability has fostered efforts to target the JBC REVIEWS: Molecular recognition of HIV TAR RNA FMN riboswitch with novel antibiotics (19,21,22,25,26). Recent structure-guided design led to the discovery of compound BRX1555-an FMN analogue that binds with a K D of 39.0 Ϯ 0.7 nM based on in-line probing (Fig.…”
Section: Model Ncrna-inhibitor Interactions: Base Pairing and Shape Cmentioning
confidence: 99%
“…Recent structure-guided design led to the discovery of compound BRX1555-an FMN analogue that binds with a K D of 39.0 Ϯ 0.7 nM based on in-line probing (Fig. 4C) (25). The ligand has an in vitro EC 50 of 1.70 Ϯ 0.18 M in single-turnover transcription termination assays and an IC 50 of 0.49 Ϯ 0.09 M in bacterial growth inhibition assays (25).…”
Section: Model Ncrna-inhibitor Interactions: Base Pairing and Shape Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have highlighted how complex structural folds in RNA molecules confer specific functions including riboswitches (Knappenberger, Reiss, & Strobel, ; Liberman et al, ; Peselis & Serganov, ; Vicens et al, ; B. Zhao, Guffy, Williams, & Zhang, ; also reviewed by Jones & Ferre‐D'Amare, ; Roth & Breaker, ), ribozymes (Chan et al, ; Costa, Walbott, Monachello, Westhof, & Michel, ; Meyer et al, ; L. A. Nguyen, Wang, & Steitz, ; Qu et al, ; Suslov et al, ; C. Zhao, Rajashankar, Marcia, & Pyle, ; also reviewed by Pyle, ; Ren, Micura, & Patel, ), and viral elements (Akiyama et al, ; Au et al, ; Imai, Kumar, Hellen, D'Souza, & Wagner, ; Keane et al, ). Additionally, recent studies have identified highly structured ncRNAs as important regulators in various cellular processes and linked misregulation of ncRNAs to important human diseases (Esteller, ).…”
Section: Introductionmentioning
confidence: 99%